PRELIMINARY STUDY OF WASTE UTILIZATION OF DRIED BANANA LEAVES AS FOOD CONTAINER WITH VARIOUS TYPES OF ADHESIVE - Aminah, Aminah; Hernawati, Hernawati; wahyuni, ayusari (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Research has been conducted entitled utilization of dried banana leaf waste as a food container with various types of adhesives. This study aims to find out the physic quality of food containers. The research method carried out was the method of analysis of food containers by testing the absorption of water with normal temperature of water and silenced for 60 minutes and for the resistance test of the container based on temperature parameters of 40ºC, 60ºC and 80ºC which in the test was silenced for 30 minutes. Both tests were given a water volume of 125 ml. From the test results of dry banana leaf containers with adhesive types of tapioca flour and sago flour has changed but can still be used and jackfruit rubber adhesive does not undergo a change in shape so that it can be used as a food container as well as synthesis adhesives do not undergo a change in shape but in its testing produces a pungent smell meaning food containers from synthetic adhesives can not be used as food containers.